Lethal and growth inhibitory activities of Neotropical Annonaceae-derived extracts, commercial formulation, and an isolated acetogenin against Helicoverpa armigera - Souza, Camila M. [UNESP]; Baldin, Edson L. L. [UNESP]; Ribeiro, Leandro P.; Silva, Ivana F. [UNESP]; Morando, Rafaela [UNESP]; Bicalho, Keylla U.; Vendramim, José D.; Fernandes, João B. (Springer Nature, 2017)
Among tropical plant families, members of Annonaceae have great potential as a source of biopesticides. To develop an alternative tool for control of Helicoverpa armigera, efficacy of ethanolic extracts from seeds of five species belonging to the genus Annona (A. montana Macfad., A. mucosa Jacq., A. muricata L., A. reticulata L. and A. sylvatica A. St.-Hil.) and an acetogenin-based commercial bioinsecticide (Anosom® 1 EC, 10,000 ppm of annonin as the main active ingredient) were evaluated in a dietary exposure bioassays. In an initial screening, an ethanolic extract from A. mucosa seeds (LC50 = 1479 ppm) and Anosom® 1 EC (LC50 = 1151 ppm) were the most promising treatments. In addition to acute toxicity, pronounced inhibition of H. armigera larval growth was observed in both treatments. Using chromatographic techniques, bioguided fractionations were conducted and the acetogenin bis-tetrahydrofuran rolliniastatin-1 was isolated as the primary compound from the most active fractions of A. mucosa. At a concentration of 41.55 ppm, rolliniastatin-1 caused total mortality of H. armigera larvae after the fourth day of exposure. In greenhouse trials, extract of A. mucosa (as an emulsifiable concentrate formulation) and the botanical insecticide based on extract of Annona squamosa L. (Anosom® 1 EC), both at LC90 values previously estimated, were compared with a diamide-based commercial insecticide (flubendiamide 480 SC) for mortality after 168 h of exposure to larvae on tomato plants; all treatments caused high larval mortality (>90%). Thus, the results of this study indicate that the derivatives of Annonaceae are a useful alternative for the integrated management of H. armigera.
Keywords: Acetogenin; Annonaceae; Botanical insecticides; Chromatographic techniques; Old world bollworm; Rolliniastatin-1